CPC-041 Direct Avoidance of Medicines Costs by Pharmaceutical Analysis of Hospital Prescriptions. (12th March 2013) - Gorce, T; Chu, N; Duhalde, V; Vie, M; Cestac, P; Bellon, B
Abstract : Background: Computerized Physician Order Entry has been set up in two digestive surgery wards in our University hospital since 2012. Clinical pharmacists analyse hospital prescriptions via this software, in order to promote good use of drugs. Purpose: To estimate avoided medicines costs, in relation to pharmacist interventions, from April to June 2012 in two surgical wards (41 inpatient beds). Materials and Methods: We focused on four types of pharmaceutical recommendations (1-to discontinue a medicine, 2-to start medicines for an untreated condition, 3-to modify a dose regimen, 4-to substitute one medicine for another). Data extracted were: daily dose, price per unit (for drug substitutions we calculated the difference between the prices of the drugs) and average length of stay. We hypothesised that our interventions had a cost impact for half of the inpatient's stay. Cost impact was calculated as follows: (Added or avoided daily dose) X (price per unit) X (half of the average length of stay). Results: 1706 prescriptions were analysed and 340 pharmacist recommendations were accepted by physicians (20%). 238 of these recommendations were among the four types listed above. 155 interventions had an impact on cost: 83% led to a cost reduction (total reduction of Euros 1949) and 17% led to an increased cost (total Euros 571). The 1378 Euros saved represent an economy of 3.6% on the total cost of medicines for these two wards between April and June 2012. Extrapolated to the entire hospital, this saving could add up to Euro 2.5 million each year. Conclusions: Medicines costs can be reduced by pharmaceutical interventions. The financial evaluation of Clinical Pharmacy practise is necessary and further studies are needed to calculate avoidable indirect costs. No conflict of interest.